Nilai·nilai Kemanusiaan Dalam Matematik Sekolah - Mohamad Zain, Shaharir (Penerbit Universiti Sains Malaysia, 2002)
Five mathematical characteristics currently listed do not possess any humanistic values. The reasons as to why there existed nonhuministic approach are listed and discussed in this paper. The need for humanistic factors in mathematics is connected to the field of ethnomathematics and humanistic mathematics in the United States.